Posicionamento e linguística forense: uma análise mediada pela Linguística de Corpus - Rodrigues, Agnes dos Santos Scaramuzzi (2016)
The overall purpose of this research was to investigate the verbal language collected and compiled in an electronic corpus, extracted from a Criminal Lawsuit - Special Part - Crimes Against the Person, Chapter I, Crimes Against Life, tried at the Legal Complex Minister Mario Guimarães Forum in the capital of São Paulo, in 2011. The relevant issue was the homicidal domestic violence. We opted for a murder case perpetrated by a male defendant against his former spouse and mother of his child, staged at the residence of the victim. The object of my study was the set of hearings that were held in two separate instances: Preliminary Hearing and Trial. Our assumption is that in a criminal proceeding, language actors fall into three distinct groups, according to their function in the proceedings: (a) charge, (b) defend and (c) judge. Because they have no access to the acts per se, only to their representations, the actors used language, largely verbal, to report their knowledge of the occurrence. In doing so, they positioned themselves in accordance with from their view of the occurrence and imbue the impact that the events have had on their lives into their accounts. Thus, there are linguistic differences in the speech of actors, according to their function in the proceedings, which can be revealed by the investigation into the stance. Revealing them can elucidate the prosecution‘s and the defense‘s versions of, for example, the profile of the victim and the defendant. Our analysis of these differences is innovative, as we did not find any study on the stance at hearings in Portuguese. As such, we seek to bridge this gap. The specific objectives were: (A) to reveal the different uses of stance by explaining their categories in two parts of speech; (A) adjectives and (b) adverbs ending in ―ly‖; and (B) to find out if there are differences in the uses of stance, according with the role the linguistic actor plays in the proceedings: (a) charge, (b) defend (c) and judge. Research questions were: 1. What is the evidence of the use of stance and its categories in the different parts of speech: (a) adjectives and (b) adverbs ending in ―ly‖? 2. Are there differences in the uses of stance in relation to the role of the linguistic actor played in the proceedings: (a) charge, (b) defend (c) and judge? The theoretical background is based on: (A) Applied Linguistics; (B) Corpus Linguistics, extracting evidence from the use of verbal language through corpus analysed electronically; (C) analysis of stance in light of Biber and Finegan (1988); Biber et al, (1999) and Biber (2006a and 2006b), defined as an expression of feeling, attitudes and judgments that the authors explains about their message; and (D) Forensic Linguistics investigating the language used in the forums. The methodology included fieldwork, use of the electronic tool WORDS and qualitative analysis. The results indicated the following: for the first question, that two stances were discovered in the two parts of speech, and for the second question, that there are differences in the uses of stances related to functions in the proceedings. Given these responses, we conclude that: (a) it is important to investigate the linguistic characteristics of each function in the proceedings in order to understand what is the language used in each of these functions; and (b) identifying different stances in forensic corpus may be useful to assess the quality of the information relayed, for example, by witnesses who impregnates their speech with personal feelings, attitudes and level of knowledge about the fact on trial. We hope to have contributed to the development of new Corpus Linguistics studies, focused on the uses of stances in forensic speech from the research methodology developed herein. We also hope to have contributed to the development of Forensic Linguistics in Brazil by offering our methodology and results, as we adopted the required rigor in our practices. Our final considerations discuss the following: the limitations, developments, future research and proposals for educational applications